Intensive Wheat Management for Yield and Quality: The Role of Variety, Environment, and Management Practices - R. P. Lollato; B. R. Jaenisch; D. Marburger (Kansas Agricultural Experiment Station Research Reports, 2019)
Management (M), variety (V), and environment (E) greatly influence wheat yield and quality. With the objective of determining the partial influence of V, E, and M, we conducted a field experiment where we imposed four management intensities to five wheat varieties during six site-years in Kansas and Oklahoma. Management intensities were 1) low-input (N fertility for a yield goal of 60 bu/a); 2) high-input (foliar fungicide, sulfur and chloride fertilizers, growth regulator, and nitrogen (N) fertility for a yield goal of 100 bu/a); 3) high-input minus fungicide; and 4) high-input minus additional N. We selected commonly grown wheat varieties with contrasting yield potential and quality characteristics. We used a split-plot design with M as whole-plots (established in randomized complete block design), and V as sub-plot (completely randomized within whole-plot). Variance component analyses suggested that E accounted for 63% of the variability in wheat yield and 55% of the variability in grain test weight; G accounted for 1 and 23% of the variability in yield and test weight, and M accounted for 1% of the variability of both. The interactions V × G and E × M accounted for 4 and 9% of the variability in yield, and 10 and 1% of the variability in test weight, respectively. Analysis of variance pooled across the entire dataset considering V and M fixed and E random suggested a significant G × M interaction on yield, which ranged from 49–61 bu/a. Meanwhile, both V and M affected test weight, which ranged from 52–58 lb/bu for the different V and from 55–57 lb/bu for the different M. These results suggest that E has the greatest impact in yield and quality, but there is room for yield improvement through V-specific M, and for quality improvement through V and M separately.
Keywords: wheat; intensive management; fungicide; nitrogen; variety